A autoconfrontação simples e a instrução ao sósia: entre diferenças e semelhanças - Rodrigues, Daniella Lopes Dias Ignácio (2010)
This paper aims in general terms at identifying similarities and differences between the methodological procedures of Self-confrontation and Instruction to the Double. More specifically, we have attempted to identify the linguistic, textual, and discursive characteristics of texts generated in and by these methodological procedures in order to contribute to the studies that use such methodologies in the analysis of teaching work. To reach our goals, we have adopted the theorical-methodological presuppositions of the Socio-discursive Interactionism (ISD) (BRONCKART, 1999, 2003, 2007, 2004, 2006, 2008), an interdisciplinary area from Psychology, which attributes a fundamental role in the human development to the acting and the language. We also assume theoretical aspects from the Ergonomics of the French Activity (AMIGUES, 2004; SAUJAT, 2005) and from the Clinic of the Activity, based on the Psychology of Work (see CLOT, 2001, 2006; CLOT et al 2001; FAÏTA, 1997, 2004, 2005; SCHELLER, 2003). The connection that we have established between these three theoretical lines, the ISD, on the one side, and on the other, the Ergonomics of the Activity and the Clinic of the Activity, is justified by the fact that they have the same theoretical framework in common, relying in founding authors such as Vygotsky, in relation to the psychological issues, and Bakhtin, in relation to the language issues. Moreover, these research lines postulate the necessity of a transdisciplinary approach in the Human/Social Sciences, questioning the division and the confinement of disciplines that have in common human and social aspects and that cannot be understood separately. We have also used categories from the Conversation Analysis, such as the types of questions in the dialogical pair question/answer, according to Kerbrat-Orecchioni's works (2006). The data collection was carried through the following procedures: i) Self-confrontation, procedure created by the linguist Daniel Faïta (1997) from the experience of confronting conductors of a high speed train (TGV) through a sequence of filmed activities (FAÏTA, 1997 e CLOT et al, 2001) and; ii) Instruction to the Double, in which instructions on how to act in the workplace are supplied to the researcher by the teacher participating in the research in a hypothetical substitution situation (ODDONE, 1981). The texts co-produced by the informants and the researcher were analyzed in the situational, organizational, and enunciative levels, according to a proposal by Machado (in print) and Bronckart (1999, 2003, 2007, 2004, 2006, 2008). The results of the analyses reveal that the text produced from the Self-confrontation is more subjective, as the informant teacher s evaluations are more explicit. On the other hand, the text of the Instruction to the Double is less subjective, as the description of the teacher participating in the research highlights the role of the prescriptions in their teaching, allowing the text to express what is necessary to the teaching acting. Thus, our research points to the necessity of developing more studies, investigations and researches on the use of such procedures